Immune tolerance induced by hematopoietic stem cell infusion after HLA identical sibling kidney transplantation - Huang, Hongfeng; Shen, Qixia; Zhou, Jingyi; Yang, Xiuyan; Cai, Qiuqin; Shen, Jia; Feng, Shi; Xie, Wenqing; Jiang, Hong; Chen, Jianghua (Frontiers in Immunology, 2022)
After the first attempt to induce operational tolerance, it has taken decades to implement it in clinical practice. Recipients with HLA identical sibling donors were enrolled. Hematopoietic stem cell infusion was done after HLA identical kidney transplantation. Three cases included were followed up for over eight years. Peri-operative conditioning protocol including anti-CD20, rabbit ATG, total lymphoid irradiation (TLI) and cyclophosphamide. Infusion of CD3+ cells and CD34+ cells was conducted. The withdrawal of immunosuppression was determined by mixed lymphocyte reaction (MLR) and graft biopsy. Case 1 and Case 2 showed persistent chimerism, while chimerism was not detected in Case 3. All three recipients showed a low-level response to donor-specific stimulation. Case 1 and Case 3 met the withdrawal rules at 16 and 32 months after transplantation, respectively. Graft function was stable, and no rejection signs were observed in routine biopsies till 94 and 61 months after transplantation. Case 2 was diagnosed with graft-versus-host disease (GVHD) 9 months after transplantation and recovered after an enhanced immunosuppression therapy. Steroids were withdrawn after one year, and 0.5 mg tacrolimus twice a day is currently the only immunosuppression at eight years and eight months. In conclusion, our clinical experience indicated the efficacy of non-myeloablative conditioning protocol for tolerance induction in HLA identical patients. Complete chimerism might be a risk factor for GVHD.